2021
DOI: 10.1007/s10658-021-02395-5
|View full text |Cite
|
Sign up to set email alerts
|

Three novel species of fungi associated with pine species showing needle blight-like disease symptoms

Abstract: band and brown spot needle blights. Needles showing spots and/or bands with fruiting bodies were sampled. From 25 pine trees samples, 82 fungal isolates were successfully retrieved. The most common fungal genera were Pestalotiopsis (42.68%, n = 35), Rhizosphaera (28.04%, n = 23) and Cladosporium (9.75%, n = 8). Seven isolates could not be assigned to a species through molecular identification by ITS sequence analysis, potentially representing novel taxa. Based on multilocus phylogenetic analyses, using ITS, tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…S3), together with a species of Diaporthe (EDNA18-0051441_MDDF_6-2_3T_ITS, GenBank OP783986). It forms a well-supported clade sister to the recently described R. pinicola (Monteiro et al, 2022) and three sequences from isolates of an unnamed Rhizosphaera species from Korea on Pinus densiflora (Figure 2). This latter species was never formally named or published, but in a conference abstract (where the species was referred to as Rhizosphaera densiflorae), the authors observed that phylogenies from Tub2 provided better resolution, and were more strongly supported by bootstrap analysis, than for ITS (Park et al, 2006) which is consistent with our findings for this genus.…”
Section: Re Sultsmentioning
confidence: 70%
“…S3), together with a species of Diaporthe (EDNA18-0051441_MDDF_6-2_3T_ITS, GenBank OP783986). It forms a well-supported clade sister to the recently described R. pinicola (Monteiro et al, 2022) and three sequences from isolates of an unnamed Rhizosphaera species from Korea on Pinus densiflora (Figure 2). This latter species was never formally named or published, but in a conference abstract (where the species was referred to as Rhizosphaera densiflorae), the authors observed that phylogenies from Tub2 provided better resolution, and were more strongly supported by bootstrap analysis, than for ITS (Park et al, 2006) which is consistent with our findings for this genus.…”
Section: Re Sultsmentioning
confidence: 70%
“…In Pinus spp., it may be characterized by shoot blight, trunk necrosis, needle blight, and pinecone decay [ 54 ]. It is not uncommon that a species of Pestalotiopsis was successfully isolated from needles of Pinus species [ 34 ]. For example, Pestalotiopsis neglecta and P. citrina isolated from Pi.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Pestalotiopsis neglecta and P. citrina isolated from Pi. sylvestris can cause the needles to turn yellow partially or completely and even cause death of the trees [ 29 , 34 ]. Pestalotiopsis bessey isolated from Pi.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… Maharachchikumbura et al (2014) selected internal transcribed spacer (ITS), partial β-tubulin (TUB), and partial translation elongation factor 1-alpha (TEF1-α), along with morphological characters to resolve the identification of Pestalotiopsis . Up to now, in a total of 92 Pestalotiopsis species have been introduced based on morphological and phylogenetic evidence ( Maharachchikumbura et al, 2014 ; Liu et al, 2019 ; Rashmi et al, 2019 ; Shu et al, 2020 ; Monteiro et al, 2022 ). Pestalotiopsis is ordinarily isolable as endophytes in plants ( Aly et al, 2010 ; Watanabe et al, 2010 ; Maharachchikumbura et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%